1987
DOI: 10.1111/j.0954-6820.1987.tb10665.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease, Serum Lipids, Platelets and Dietary Fish in Two Communities in Northern Norway

Abstract: Coronary heart disease (CHD) mortality was registered in an inland and a coastal community in Northern Norway. Subgroups of healthy males from the communities were investigated further. The daily consumption of fish in the coastal and inland areas was 132.4 g and 55.1 g respectively, and the intake of eicosapentaenoic acid was 0.9 g and 0.25 g. The content of n‐3 polyunsaturated fatty acids in platelet phospholipids and primary bleeding time were similar in the two groups. Linoleic acid was lower and saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Furthermore, the addition of 12-LOX products (12-HETE and 12-HPETE) to human islets resulted in a decrease in glucose-stimulated insulin secretion associated with a decrease in islet viability (Persaud et al, 2007), and a partial restoration in glucose-stimulated insulin secretion if 12HETE was combined with lisofylline, an inhibitor of IL-12 signaling. Collectively these data support a predicted role of IL-12 in mediating the immune damage caused by the 12-LOX pathway (Simonsen et al, 1987; Vidgren et al, 1997; Vognild et al, 1998). …”
Section: Oxylipins and Diabetessupporting
confidence: 76%
“…Furthermore, the addition of 12-LOX products (12-HETE and 12-HPETE) to human islets resulted in a decrease in glucose-stimulated insulin secretion associated with a decrease in islet viability (Persaud et al, 2007), and a partial restoration in glucose-stimulated insulin secretion if 12HETE was combined with lisofylline, an inhibitor of IL-12 signaling. Collectively these data support a predicted role of IL-12 in mediating the immune damage caused by the 12-LOX pathway (Simonsen et al, 1987; Vidgren et al, 1997; Vognild et al, 1998). …”
Section: Oxylipins and Diabetessupporting
confidence: 76%
“…These include improved triglycerides, 44 anti-inflammatory, antithrombotic and antiatherogenic effects of fish oil. 59 Of further interest, a lower prevalence of diabetes [60][61][62][63][64] and glucose intolerance 65 have been reported in populations known to have a very high omega-3 fatty acid intake (for example, Greenland, Alaska, Faroe Islands). An inverse correlation between omega-3 intake and conditions such as diabetes and glucose intolerance has been observed in an elderly Dutch population.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand there is low prevalence of diabetes in Greenland [6] and Alaskan Eskimos [7] as well in people living in the Faeroe Islands [8], populations known for a very high intake of omega-3 fatty acids. The prevalence of diabetes mellitus in Alaska has found that 15.7/1000 subject was lower than over United States vat of 24.7/1000 and 8.8/1000 among Alaskan Eskimos [9].…”
Section: Introductionmentioning
confidence: 99%